Implementation of Problem Based Learning (PBL) Based Local Materials (LM) Through Lesson Study (LS) to Enhance Metacognition Skill, Inquiry Skill and Cognitive Learning Outcomes on Plantae Topic in Grade X5 SMAN 1 Mojo Kediri - Yuliani Yuliani; Enggar Wahyuningtyas; Poppy Rahmatika Primandiri; Agus Muji Santoso (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The research was aimed to know the implementation of PBL based LM through LS to improve metacognitive skill. It was determined using metacognitive skill rubric on 6 categories. Inquiry skill was measured using observation checklist and devided into 5 categories. Cognitive learning outcomes was measured by essay test and  compared using KKM. This research was conducted by collaboration classroom action research and lesson study.  This research consisted of two cycles and started in March to April 2015. The result of this research shown that student metacognitive skill increased from first cycles to seconds cycles and inquiry skills of students increase in both categories from 3.33% to 46,67%, while the yet catogory was decreased from 30% to 20%, Cognitive learning outcomes increased from 52% to 76,77%.Keywords: Problem Based Learning, Local Materials, Lesson Study, Inquiry Skill, Metacognitive Skill